2016
DOI: 10.1088/0957-4484/27/19/195402
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites of TiO2/cyanoethylated cellulose with ultra high dielectric constants

Abstract: A novel dielectric nanocomposite containing a high permittivity polymer, cyanoethylated cellulose (CRS) and TiO2 nanoparticles was successfully prepared with different weight percentages (10%, 20% and 30%) of TiO2. The intermolecular interactions and morphology within the polymer nanocomposites were analysed. TiO2/CRS nanofilms on SiO2/Si wafers were used to form metal-insulator-metal type capacitors. Capacitances and loss factors in the frequency range of 1 kHz-1 MHz were measured. At 1 kHz CRS-TiO2 nanocompo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…The minimum value of LC occurs on 0.4% filler loading. This pattern of increasing LC with the increase in TiO 2 concentration has been also reported by Madusanka et al [31].…”
Section: Leakage Currentsupporting
confidence: 87%
“…The minimum value of LC occurs on 0.4% filler loading. This pattern of increasing LC with the increase in TiO 2 concentration has been also reported by Madusanka et al [31].…”
Section: Leakage Currentsupporting
confidence: 87%
“…For polymer/ceramic filler composites, the improved dielectric permittivity is mainly ascribed to the interfacial polarization, also known as the Maxwell-Wagner effect [23][24][25]. In this work, for DCFs-Filtering, the enhancement of dielectric permittivity is attributed to high loading of BaTiO 3 nanoparticles and in particular remarkable interfacial polarization from good dispersion.…”
Section: Resultsmentioning
confidence: 71%
“…Additionally, an additional PVP capping layer with a thickness below 50 nm suppressed leakage current to below 10 −7 A cm −2 at ±3 V without a significant loss of capacitance. 230 Amaratunga et al 231 reported cyanoethylated cellulose-based dielectric nanocomposites with ultrahigh dielectric constants exceeding 100 with TiO 2 NP loadings of 10% to 30%. The high dielectric constants, which exceed both the embedded nanofillers (TiO 2 ) and the polymer matrix, were attributed to the specific HOMO−LUMO energy alignments between TiO 2 and the cyanoethylated cellulose.…”
Section: Polymer Nanocomposite Gate Dielectricsmentioning
confidence: 99%